Encyclopedia of cancer - Bertino, Joseph R. (Gale virtual reference library., 2002)
Since the publication of the first edition of the Encyclopedia of Cancer, an amazing amount of new information has been disseminated in the field of cancer research. This second edition strives to capture the advances occurring in the etiology, prevention, and treatment of cancer, from basic science to clinical application. By providing concise expositions on a broad range of topics, the Encyclopedia is an excellent resource for those seeking information beyond their specific areas of expertise. Written by a distinguished panel of authors, entries cover a variety of aspects of cancer such as oncology, immunology, epidemiology, gene therapy, oncogenes/tumor suppressor genes, and pharmacology. This outstanding reference is essential for anyone involved in the study or treatment of cancer. An online version of the Encyclopedia of Cancer is available on ScienceDirect. Visit http://info.sciencedirect.com/reference_works/ for contact and subscription information. Access options are available even if you're not an existing ScienceDirect customer! Key Features * Covers all aspects of cancer, segueing from basic science to clinical topics * Includes an additional volume to incorporate all the new advances in the etiology, prevention, and treatment of cancer made since the first edition * Convenient organization employs standard entry format for quick and easy reference * Extensive cross-referencing provides reader with broader range of knowledge * Contributions solicited from among the top names in a variety of fields.